Systemic neurotransmitter responses to clinically approved and experimental neuropsychiatric drugs. Issue 1 (December 2018) - Noori, Hamid; Mervin, Lewis; Bokharaie, Vahid; Durmus, Özlem; Egenrieder, Lisamon; Fritze, Stefan; Gruhlke, Britta; Reinhardt, Giulia; Schabel, Hans-Hendrik; Staudenmaier, Sabine; Logothetis, Nikos; Bender, Andreas; et al.
Abstract Neuropsychiatric disorders are the third leading cause of global disease burden. Current pharmacological treatment for these disorders is inadequate, with often insufficient efficacy and undesirable side effects. One reason for this is that the links between molecular drug action and neurobehavioral drug effects are elusive. We use a big data approach from the neurotransmitter response patterns of 258 different neuropsychiatric drugs in rats to address this question. Data from experiments comprising 110, 674 rats are presented in the Syphad database [www.syphad.org ]. Chemoinformatics analyses of the neurotransmitter responses suggest a mismatch between the current classification of neuropsychiatric drugs and spatiotemporal neurostransmitter response patterns at the systems level. In contrast, predicted drug–target interactions reflect more appropriately brain region related neurotransmitter response. In conclusion the neurobiological mechanism of neuropsychiatric drugs are not well reflected by their current classification or their chemical similarity, but can be better captured by molecular drug–target interactions. The precise relationship between neurobehavioural effects and neurotransmitter effects of psychiatric drugs are not always understood. Here the authors develop a database documenting the neurotransmitter response in rats to 258 different neuropsychiatric drugs, and conclude that this neurotransmitter response does not, in general, reflect the current categorisation of those drugs.